Odpowiedzi

2009-11-22T11:49:14+01:00
A) x2-6x=x(x-6)
b)3y2+6y-12=3(y2+2y-4)
c)2t3-6t2+4t=2t(t2-3t2+2t)
d)5r2/6+r/3=r/3(5r/2*1)
e)x/2+1/x=x(1/2+1/1)
f)4x2+2/x=2x(2x+1/x2)
1 5 1
  • Abum
  • Początkujący
2009-11-22T11:56:52+01:00
A) x (x+6)
b) 3 (y²+2y-4)
c) 2t (2t²-3t+2)
d)r/3(5r/2+1)
e)x(½+1/x²)
f)2x(2x+1/x²)
1 1 1
2009-11-22T11:57:23+01:00
Włącz przed nawias czynnik podany bok.()
a)x²-6×= (x)(x-6)
b)3y²+6y-12 =(3)(y²+2y-4)
c)2t³-6t²+4t =(2t)(t²-3t+2)
d)5r²/6 + r/3= (r/3)(5/2r+1)
e)x/2 + 1/x =(x)(1/2 +1/7)
tu brak cyfry np.7
lub mialo tak byc
x/2 + 1/x =(x)(1/2 +1/x²)
f)4x²+2/x= (2x)(2x+1/x²)
1 1 1